Letras portuguesas en la biblioteca del conde de Gondomar - Pablo Andrés Escapa (E-Spania)
The collection of Portuguese books gathered by Diego Sarmiento de Acuña, I Count of Gondomar (1567–1626), stands out as the richest private collection of Portuguese written culture extant in early modern Spain, offering a fruitful avenue of research for tracing the reception of Portuguese culture in Spain. An in-depth analysis of Gondomar’s library catalogues as they are preserved today will shed light on the substantial increase of Portuguese books in his collection from 1593 onwards. Further evidence of Gondomar’s interest and affection for the Portuguese language can be found in his letters, which show an exclusive fondness not seen in his approach to other languages. His letters also allow us to reconstruct the different commercial operations required for acquiring Portuguese books for both his collection and for other collectors in Spain and abroad. Diego de Silva y Mendoza, Count of Salinas, played a fundamental role in the exchange and purchase of these books, demonstrating a common interest in Portuguese manuscripts and printed books.